Rewrite in simplest radical form the problem in the image below. Show and explain each step. Thank you for your time and help.
![Rewrite in simplest radical form the problem in the image below Show and explain each step Thank you for your time and help class=](https://us-static.z-dn.net/files/ddb/82edf18679d3eb559c568b4e2f3174eb.png)
Answer:
Hello,
Step-by-step explanation:
[tex]\dfrac{x^{\frac{5}{6}} }{x^{\frac{1}{6}} } \\\\=x^{\frac{5}{6} -\frac{1}{6} }\\\\=x^{\frac{4}{6} }\\\\=x^{\frac{2}{3} }\\\\=\sqrt[3]{x^2}[/tex]